(untitled) (Journal of Oriental Studies, 2016)
The international migration and issues of labor migrants is now become one of the important social and political issues of many countries. Previously a country of emigration, the Republic of Korea has now become a net migrant receiving country.The evolving migration landscape in Korea and the development of new immigration policies have had a significant impact on Korean society. In this context, it is both highly relevant and timely to take stock of recent trends in migration and migration-related policies for Korea, and to use that perspective to inform policies that anticipate and prepare for potential future challenges. This article discusses the social and political welfare of labor migrants in South Korea.